Low occurrence of bacteria on the lift buttons of a public hospital executing weekly Covid 19 decontamination - Muhammad, Izzati; Raja Abdul Rahman, Raja Noor Zaliha; Samsuddin, Niza; Kamarudin, Norhidayah; Alias, Norsyuhada (2021)
Introduction: The ongoing pandemic of coronavirus disease 2019 (COVID 19) has led to serious changes in the way of handling common touch objects. Since these objects had the potential to become fomite, the Malaysian Ministry of Health had implemented sanitation and decontamination as a must routine especially for public spaces such as hospitals to prevent any chances of getting nosocomial infection. However, there was little to no publication on the effect of these implementations on common touchable surfaces in Malaysia. Objectives: This research was conducted to quantify the bacteria isolated from the interior and exterior lift buttons of a public hospital in Kuantan, Pahang that performed weekly Covid 19 cleaning and decontamination Methodology Sampling using cotton swabs was conducted thrice with two weeks intervals from March to April 2021 on the lift buttons in the main building of the hospital by purposive sampling technique (n=50). The samples were processed in the laboratory as per standard microbiological procedures Results: The average percentage of bacterial occurrence was 34.8%. Bacteria on the interior lift buttons were more abundant than on the exterior lift buttons with 440 and 120 CFU/mL, respectively. The distribution of bacteria on the lift buttons was skewed towards Gram-positive bacteria (84.1%) when compared to Gram-negative bacteria (15.9%) wherein cocci-shaped bacteria dominated with 79.6% occurrence. Conclusion: The low quantity of bacteria on the lift buttons showed that the weekly routine decontamination was effective. The decontamination method is ideal to be applied in public places to minimise the occurrence of contaminants.